RANCANG BANGUN ALAT KONTROL BEBAN ELEKTRONIK DIGITAL PADA PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) OFF-GRID - Effendy, Machmud (Jurnal Gamma, 2012)
RANCANG BANGUN ALAT KONTROL BEBAN ELEKTRONIK DIGITAL PADA  PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMh) OFF-GRIDMachmud EffendyStaf Pengajar Jurusan Teknik Elektro, Fakultas Teknik Universitas Muhammadiyah MalangEmail: machmudeffendy@yahoo.comABSTRACTElectronic load control device (ELC) at the MHP Digital Off-Grid (not connected to the PLN) replaces previous controls are still using analog systems (Machmud, 2008), because analog systems have drawbacks including: difficult to perform the initial setup of the generator voltage stability in the event of changes in consumer loads, so that the percentage error generator voltage and frequency stability is still quite large. In 2010 (Machmud) makes ELC models using Matlab with the PI system that is able to stabilize the voltage of the generator at the second to 8.These results continue the previous research by designing wake ELC using microcontroller system that is equipped with PID control. Series of ELC supporters were also made, among others: the sensor circuit voltage, zero detection circuit, and electronic switch circuit. Voltage sensor circuit that has been made to have the voltage linearity level of 0.997. While the time required to trigger the triac with a maximum of 1000 Ohm load is between 0 to 10 milliseconds.PID system is created using the C language and loaded into the microcontroller IC is able to stabilize the voltage generator in the event of changes in the electrical load. With menggunakann value Kp = 4, Ki = 0:01, the system is able to stabilize the voltage of the generator in the event of changes in the electrical load 100 and 500 Ohm 0hm in seconds to 8 parameters Kp in PID control system is applied to the electronic load control devices MHP does not cause changes significant at keluran controller, so its value can be ignored.keyword: PLTMh, Digital Control